Comparison between Numerical and Analytical Analysis of the Dynamic Behavior of Circular Tunnels - Qingrui Lu; Shijun Chen; Yi Chang; Chunfeng He (Earth Sciences Research Journal)
Dynamic behavior of underground structures is controlled by the strain field imposed by wave propagation and by the interaction between rock mass and structures. Shear and pressure waves propagating in the plane of the cross-section of the tunnel generate ground distortions, which tend to cause ovaling deformations of the lining. In this paper, the seismic response of a circular tunnel subjected respectively to shear waves and pressure waves will be analyzed both analytically and numerically at first, and then a complete 3D analysis will be given to show the overall effects on a tunnel induced by seismic events considering seismic inputs in three directions.